Evidence for the decay B0→J/ψω and measurement of the relative branching fractions of B0s meson decays to J/ψη and J/ψη′ - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Dordei, Francesca; Eisele, Franz; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Nuclear physics. B, Particle physics, 2013)
First evidence of the B0→J/ψω decay is found and the Bs0→J/ψη and Bs0→J/ψη′ decays are studied using a dataset corresponding to an integrated luminosity of 1.0 fb−1 collected by the LHCb experiment in proton-proton collisions at a centre-of-mass energy of s=7 TeV. The branching fractions of these decays are measured relative to that of the B0→J/ψρ0 decay:B(B0→J/ψω)B(B0→J/ψρ0)=0.89±0.19(stat)−0.13+0.07(syst),B(Bs0→J/ψη)B(B0→J/ψρ0)=14.0±1.2(stat)−1.5+1.1(syst)−1.0+1.1(fdfs),B(Bs0→J/ψη′)B(B0→J/ψρ0)=12.7±1.1(stat)−1.3+0.5(syst)−0.9+1.0(fdfs), where the last uncertainty is due to the knowledge of fd/fs, the ratio of b-quark hadronization factors that accounts for the different production rate of B0 and Bs0 mesons. The ratio of the branching fractions of Bs0→J/ψη′ and Bs0→J/ψη decays is measured to beB(Bs0→J/ψη′)B(Bs0→J/ψη)=0.90±0.09(stat)−0.02+0.06(syst).
Im Titel ist "0" jeweils hochgestellt und "s" in B0s tiefgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 586
Available online 27 October 2012
Gesehen am 23.03.2021